A comparison of EFL students and instructors’ written feedback preferences and reported practices at a Moroccan university - Mamad, Abderrahim; Vígh, Tibor (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée, 2025)
This study aimed to investigate university students’ preferences for and reported instructor practices of written feedback (WF) and how these align with instructors’ perceptions and self-reported practices in EFL writing classrooms. An 80-item survey was conducted with 13 instructors and their 210 students at a Moroccan university. The findings revealed that instructors’ perceptions aligned with students’ preferences for judgmental WF on the written text and all process-based WF subscales. However, instructors considered WF modes on the written text more important than students. In terms of practices, instructors reported employing certain WF practices (judgmental WF on the written text, content-based WF related to textuality standards, and macroaspects of writing) more often than students reported. The study emphasizes the importance of aligning classroom WF practices with students’ preferences to enhance writing performance.